2019
DOI: 10.3390/su11082195
|View full text |Cite
|
Sign up to set email alerts
|

Construction Cost of Green Building Certified Residence: A Case Study in Taiwan

Abstract: The green building certification system of Taiwan, EEWH (Ecology, Energy Saving, Waste Reduction and Health), has been in operation for more than 20 years (since 1999). In order to understand the relationship between green building certification and the construction costs of residential buildings, this study obtained 37 green building-certified residential cases and 36 general residential cases available from public information and conducted a comparative analysis. The results of this study showed that the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
(51 reference statements)
0
13
0
1
Order By: Relevance
“…Even though a section of the literature attributed the high-cost of GB to green features, sustainability concern is a negligible aspect of the total building systems (Emmanuel, 2011). Moreover, as ordinary certification is possible at a lower extra cost than feared (Ekung, 2019; Sun et al , 2019), CMs correlates with the misunderstanding of cost factors. The substance of extra cost is soft costs-dependent (Abidin and Azizi, 2016), hence, linking high-cost to hard cost is both overvalued and overestimated beliefs (Kovach et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though a section of the literature attributed the high-cost of GB to green features, sustainability concern is a negligible aspect of the total building systems (Emmanuel, 2011). Moreover, as ordinary certification is possible at a lower extra cost than feared (Ekung, 2019; Sun et al , 2019), CMs correlates with the misunderstanding of cost factors. The substance of extra cost is soft costs-dependent (Abidin and Azizi, 2016), hence, linking high-cost to hard cost is both overvalued and overestimated beliefs (Kovach et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported a cost premium greater than 15% to show that CMs exist in communicating the cost of GB. Against the reported high-cost premiums, ordinary certification is achievable at zero extra cost (Ekung, 2019;Sun et al, 2019). The costs could be cheaper or equal to the costs of an alternate construction approach (Sherwin, 2006;Mapp et al, 2011;Dobson et al, 2013).…”
Section: Cost Misperceptions and Their Factual Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The varieties of value and cost-saving encountered run parallel with making plans and design of the building. [49] Initial cost reduction…”
Section: Energy Cost Savingmentioning
confidence: 99%
“…One the other hand, a study created a model to identify a powerful driver of the housing market: the ability of young households to afford the down payment on a starter home, and in particular, their income [34]. There is even a study that shows that higher-income households exhibit a higher willingness to pay for green features (ecolabelled buildings) [35], even if the results of the study show that the cost of a building with a green label is not more expensive [36]. One paper focusing on house prices and household income in Taiwan found that the slow increase in income may just sustain the long-run trend in house prices [37].…”
Section: • Average Household Monthly Incomementioning
confidence: 99%